3D automated quantification of epidermal thickness and dermal heterogeneity in high-definition optical coherence tomography: Illustrative utility in morphea - Lim, Gim Hui (2022)
Scleroderma is the most common form of fibrotic disease involving the skin, and the subtype that only affects the skin is known as morphea. The conventional investigation for cutaneous fibrotic diseases is skin biopsy, an invasive ex vivo procedure. Typically, another biopsy of adjacent normal skin is required for comparison, in order to visualize the excessive dermal collagen deposition. Optical coherence tomography has been shown to be useful in fibrotic skin disorders, in obtaining in vivo cross-sectional visualization.1-3 The high-definition optical coherence tomography (HD-OCT) (Skintell®) developed more recently allows imaging with an enhanced resolution of 3µm in both axial and lateral planes and has an imaging depth of 570 µm.